A highly efficient heterogeneous catalyst of cobalt-based coordination polymers for aerobic epoxidation of cyclohexene. Issue 34 (15th August 2018) - Yu, Fan
Abstract : A novel heterogeneous catalyst of cobalt-based coordination polymers using a tyrosine-based derivative has been successfully constructed, and it exhibits high catalytic activity in changing the reaction pathway and lowering the activation energy to 25.5 kJ mol −1 . Abstract : A novel heterogeneous catalyst of cobalt-based coordination polymers has been successfully fabricated using a tyrosine-based derivative. Heterogeneous catalytic experiments on allylic oxidation of cyclohexene indicate that the titled complexes present high catalytic activities using tert -butyl hydroperoxide ( t -BuOOH) as an oxidant. The activation energy for the whole process of oxidation of cyclohexene has been calculated to be 25.5 kJ mol −1, which indicates the important role of the selected ancillary ligands in the synthesis of the heterogeneous catalyst.